2019
DOI: 10.5937/nasvas1901035g
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of English language test tasks for seventh and eighth-graders in Serbia according to Bloom's Taxonomy

Abstract: Cognitive processes are the foundation of the cognitive domain of critical thinking. Even though developing these processes is an educational priority in many countries, including Serbia, the concept itself and the ways in which these cognitive actions can be assessed are left to teachers to discover. The aim of this paper is to investigate what cognitive processes are required of seventh-and eighth-graders in Serbia in order to complete the tasks included in English language tests. The authors collected 14 te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Hence, we must not jump to the conclusion that the participant teachers never require, or offer opportunities to, their students to use the language for communicative purposes. Still, these results, as well as those obtained by Glušac, Pilipović, and Marčićev (2019) relating to a nearly identical analysis of the subsequent two grades, clearly indicate that there is a tendency among English language teachers in Serbia towards a structuralist approach. The results necessitate familiarizing Serbian English language teachers with the notion, teachability, and testing principles of CT, as well as informing them about the benefits and pitfalls of the predominant testing approach they seem to have adopted in order to ensure quality teaching of CT and quality foreign language testing.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Hence, we must not jump to the conclusion that the participant teachers never require, or offer opportunities to, their students to use the language for communicative purposes. Still, these results, as well as those obtained by Glušac, Pilipović, and Marčićev (2019) relating to a nearly identical analysis of the subsequent two grades, clearly indicate that there is a tendency among English language teachers in Serbia towards a structuralist approach. The results necessitate familiarizing Serbian English language teachers with the notion, teachability, and testing principles of CT, as well as informing them about the benefits and pitfalls of the predominant testing approach they seem to have adopted in order to ensure quality teaching of CT and quality foreign language testing.…”
Section: Resultssupporting
confidence: 65%
“…When these results are compared with those obtained by Glušac, Pilipović, and Marčićev (2019), who investigated the levels of cognitive capacity required in English language tests for seventh and eighth graders, it is obvious that there is a tendency among English language teachers in Serbia to design tests that are comprised predominantly of low-level thinking tasks. In the analyzed tests for the seventh and the eighth grade there was also a paucity of tasks requiring higher levels of cognitive operation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the results of a study conducted by Mirkov and Gutvajn (2014) indicated that Serbian eighth-graders were dissatisfied with the number of opportunities for developing their CT skills. Along the same lines, Glušac, Pilipović and Marĉićev (2019) discovered that English language teachers in Serbia did not seem to possess adequate skills for assessing their students' progress in the acquisition of domain-specific CT skills, which is an important prerequisite for successful teaching and learning.…”
Section: Resultsmentioning
confidence: 99%